Can AI Improve Surgical Team Coordination? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
The modern operating room is a symphony of precision, expertise, and, most importantly, teamwork. The seamless coordination of surgeons, anesthesiologists, n...
Keywords: AI in Surgery and Robotics; Improve; Surgical; Coordination; Artificial Intelligence; Machine Learning; Healthcare